2014
DOI: 10.1179/0001551213z.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the incidence of gestational diabetes and neonatal outcomes using the IADPSG guidelines in comparison with the Carpenter and Coustan criteria in a Belgian general hospital

Abstract: We have conducted a systematic universal screening for gestational diabetes mellitus (GDM) since 2008, following the criteria outlined by the International Association of Diabetes and Pregnancy Study Group (IADPSG) since 2011. However, we recently replaced the IADPSG standards with those established by the Belgian French Language Gynecologists and Obstetricians Group (GGOLFB). These new criteria indicate GDM when fasting plasma glucose (FPG) is ≥0·92 g/l at the beginning of pregnancy or when an orally provoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
4
6
0
1
Order By: Relevance
“…Our retrospective study demonstrated a 2.5-fold increase in the diagnosis of GDM with the implementation of IADPSG criteria, with no statistically significant differences in maternal or neonatal outcomes. This result has been similarly reported in two other studies (12,13). …”
Section: Resultssupporting
confidence: 91%
“…Our retrospective study demonstrated a 2.5-fold increase in the diagnosis of GDM with the implementation of IADPSG criteria, with no statistically significant differences in maternal or neonatal outcomes. This result has been similarly reported in two other studies (12,13). …”
Section: Resultssupporting
confidence: 91%
“…Several prospective non‐RCTs or retrospective studies comparing the incidence of GDM and/or outcomes between the One Step and Two Step methods have also been published . Polled data of these studies show that GDM‐positive women at One Step test, when treated, have better maternal and neonatal outcomes, compared with treated women GDM positive at Two Step test.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the GDM prevalence rate in Australia was 13.0% when using the IADPSG standard, with 82% sensitivity and 94% specificity (4). The Oriot et al study (5) reported that the GDM prevalence rate ranged from 8-23% according to the IADPSG standard, and these patients required insulin therapy. The prospective studies of Nayak et al indicated that the GDM prevalence rate was 27% by applying IADPSG standard screening, and the number of pregnancy complications increased in the GDM group [25% vs 12%] (6).…”
Section: Discussionmentioning
confidence: 98%